A Single-Chip 15-32 GHz Signal Source in SiGe Bipolar Technology - Nehring, Johannes; Nasr, Ismail; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (European Microwave Integrated Circuits Conference (EuMIC), 2013)
This paper presents a single-chip octave-bandwidth signal source covering a frequency band from 15GHz to 32GHz. The circuit was fabricated in a 0.35 μm SiGe bipolar technology with an ft/fmax = 170/250GHz. An array of four crosscoupled voltage controlled oscillators with subsequent frequency ranges is implemented. The oscillator cores only draw 13mA from a 3.3V supply. Another 13mA is drawn by following buffer stages. A 4-to-1 multiplexing amplifier acts as a combiner providing the octave-wide bandwidth at a single differential output. The output power was measured to be between -2.5 dBm and 0.7 dBm. The signal source provides a good phase noise performance of -105 dBc/Hz at 15GHz and -96.8 dBc/Hz at 30GHz at an offset of 100MHz from the carrier frequencies. The overall circuit consumes a total power of 205mW and occupies a chip area of 1128 μm x 1028 μm.
elib2cris::1512001600,nehring2013
Keywords: VCO; signal source; wideband; microwave; octave-wide bandwidth